Statistical data analysis based on the L1-norm and related methods selected papers - Dodge Yadolah ed.; International Conference on Statistical Analysis Based on the L1-Norm and Related Methods (4th : 4-9 Aug 2002 : Neuchatel,Switzerland); International conference on statistical analysis based on the L1-norm and related methods Neuchatel, Switzerland 4-9 Aug 2002 (Basel Birkhauser Verlag, 2002)
This volume deals with the importance of development of theory, methods and applications related to the statistical data analysis based on the L1-norm. It is organized into seven thematic parts: such as All about quantiles, Financial statistics and time series, Estimation, testing and characterization, Deep in the data, Classification, Density estimation and image processing and lastly Regression models in environmental studies.
Keywords: Statistical data analysis